ROLE AND IMPORTANCE OF THE INSTITUTE OF MEDIATION IN DISPUTE RESOLUTION (Scientific journal of the Fergana State University, 2023)
Mediation is a process in which an independent, impartial third party, known as a mediator, negotiates and helps both parties resolve a dispute using mediation techniques. This article highlights the role and importance of the institution of mediation in conflict resolution.